Antiplasmodial β-triketones from the flowers of the Australian tree Angophora woodsiana. Issue 11 (1st June 2017) - Senadeera, Sarath P.D.; Duffy, Sandra; Avery, Vicky M.; Carroll, Anthony R.
Graphical abstract: Highlights: Australian Eucalypt, Angophora woodsiana yielded two new and nine knownβ-triketones. Woodsianone A contains a cadenine sesquiterpene conjugated to syncarpic acid. Woodsianione B is the first simple β-trikeone to contain an epoxide group. Anti-plasmodial activity observed for several of the β-triketone and SAR is observed. Abstract: Chemical investigations of the MeOH extract of air dried flowers of the Australian tree Angophora woodsiana (Myrtaceae) yielded two new β-triketones, woodsianones A and B (1, 2 ) and nine known β-triketones (3 –11 ). Woodsianone A is a β-triketone-sesquiterpene adduct and woodsianone B is a β-triketone epoxide derivative. The structures of the new and known compounds were elucidated from the analysis of 1D/2D NMR and MS data. The relative configurations of the compounds were determined from analysis of 1 H– 1 H coupling constants and ROESY correlations. All compounds (1 –11 ) had antiplasmodial activity against the chloroquine sensitive strain 3D7. The known compound rhodomyrtone (5 ) and new compound woodsianone B (2 ) showed moderate antiplasmodial activities against the 3D7 strain (1.84 µM and 3.00 µM, respectively) and chloroquine resistant strain Dd2 (4.00 µM and 2.53 µM, respectively).